PENERAPAN PIDANA DENDA DALAM TINDAK PIDANA KEIMIGRASIAN PASAL 71 JO. PASAL 116 UNDANG-UNDANG NO. 6 TAHUN 2011 TENTANG KEIMIGRASIAN (PUTUSAN NO.11/Pid.C/2016/PN.JKT.BRT) - Abdullah, La Ode Dedi (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
Immigration is a crime that violates the law and is protected by the law with immigration activities. The application of criminal fines for immigration offenses by not carrying out their obligations as foreigners residing in the Territory of the Republic of Indonesia, as requested by Article 71 of Law No. 6 of 2011 concerning Immigration, which reads "Every Foreigner residing in Indonesian territory is obliged to Invite travel documents or residence permits that are requested for refunds by an Immigration Officer approved for Immigration supervision". Regarding immigration actions which emphasize the sanctions of his government, so considering the consideration of the formulation of court sentences will result in ineffectiveness of immigration laws that are less effective because foreigners (convicts) can choose the appropriate protection with legal entities.